Coal dust, Lycopodium and niacin used in hybrid mixtures with methane and hydrogen in 1 m(3) and 20 l chambers - Janovský, Břetislav; Skřiňský, Jan; Cupák, Jan; Vereš, Jan (My University, 2019)
The aim of the work presented here is a comparison of hybrid mixture explosion parameters obtained in the explosion chambers used in European Standard EN 14034 and explore the influence of the explosion volume and the ignition source on the explosion parameters of the hybrid mixtures. Explosion chambers of the two volumes, 20 l and 1 m³, specified in the Standard, were used to carry out standard procedures according to EN 14034 to determine hybrid mixture explosion parameters such as maximum overpressure and maximum rate of pressure rise. Three flammable dusts widely accepted as standards were chosen – Pittsburgh seam bituminous coal dust, Lycopodium Clavatum spores and Niacin. Two flammable gases (methane and hydrogen) were used. Methane and hydrogen are used for standard testing of flammable gas mixtures explosion parameters in explosion chambers. The explosion parameters of various mixtures of flammable dusts, flammable gases and air were measured. Standard ignition sources for dust dispersion, two 5 kJ chemical igniters, were used in both chambers. Explosion parameters were also measured using the standard permanent spark described in EN 15967 as an ignition source for a comparison of the effect of different ignition energies on explosion parameters. The results show a significant increase of normalised maximum rates of pressure rise in a 20 l chamber compared with a 1 m³ chamber caused by higher turbulence levels in the smaller chamber. It was also shown that the permanent spark could be used for easily ignitable dusts and, in some cases, can produce even higher rates of pressure rise than chemical igniters.
Uhelný prach, Lycopodium a niacin použitý v hybridních směsích s methanem a vodíkem ve výbuchových komorách 1 m3 a 20 l
Keywords: hybrid mixture; 20 l chamber; 1 m3 chamber; EN 14034; ignition source; hybridní směs; komora 20 l; komora 1 m(3); EN14034; iniciační zdroj